Education of Young Adults and the Elderly -subjects of rights of a political-pedagogical education - Sara Ingrid Borba (Universidade Estadual de Alagoas, 2021)
This text is the result of preliminary studies on the education of young adults, in a context that perceives the existence and strong discourse in defense of the Common Base of National Curriculum -BNCC, for the various levels of basic education, prepared with a view to to the new educational demands. But it is worth questioning why Youth Education, Adults -EJA, is not being considered in this new curricular implementation and how is the situation of its issues? As a State public policy, we seek to strengthen the learning rights of Brazilian students, However, we do not see the rights of the EJA subjects contemplated according to their specificities, including the discussion on the presence of the elderly in the context of this teaching modality. The Education of Young Adults and Elders -EJAI is a guarantee of the right of access to public and quality education for those who could not study at the appropriate age, provided for in the Federal Constitution of 1988 and in the LDB (9394/96) and other public policies. ANPED GT 18 documents were also taken as a starting point for critical reflection, as well as the research already carried out with thistype of criticality. In the reflection on the relationship of the EJA and Popular Education as its own policy, with its curriculum and its own philosophical and political references, as well as its foundations and pedagogical didactic strategies, which are based on the perspective of La Freiriana. Therefore, the descriptive qualitative type was investigated. As conclusive aspects, it presents proposals to broaden the debate on popular education in defense of the education for all proposal, highlighting theimportance of considering and respecting EJA issues as rights issues as opposed to the processes of denial and exclusion that permeate this mode of basic education